2020
DOI: 10.1021/acs.jctc.0c00736
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a Dressed Coupled-Cluster Method with Implicit Triple Excitations and Benchmark Application to Hydrogen-Bonded Systems

Abstract: In this paper, we present a coupled-cluster theory based on a double-exponential wave operator ansatz, which is capable of mimicking the effects of connected triple excitations in an iterative manner. The triply excited manifold is spanned via the action of a set of scattering operators on doubly excited determinants, whereas their action annihilates the Hartree−Fock reference determinant. The effect of triple excitations is included at a computational scaling slightly higher than that of conventional coupled-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Szakács and Surján 5,6 , for the first time, demonstrated that the CC iteration scheme under an input perturbation shows chaotic dynamics. Some of the present authors had shown that the dynamics associated with a double similarity transformed CC [7][8][9] iterations follows the universality of time-discrete map of one-parameter family. The authors analysed the phase space trajectory under an input perturbation and demonstrated a full period-doubling bifurcation cascade that precedes the onset of the chaos.…”
Section: Introductionmentioning
confidence: 57%
“…Szakács and Surján 5,6 , for the first time, demonstrated that the CC iteration scheme under an input perturbation shows chaotic dynamics. Some of the present authors had shown that the dynamics associated with a double similarity transformed CC [7][8][9] iterations follows the universality of time-discrete map of one-parameter family. The authors analysed the phase space trajectory under an input perturbation and demonstrated a full period-doubling bifurcation cascade that precedes the onset of the chaos.…”
Section: Introductionmentioning
confidence: 57%
“…We refer to eq as the Flexible Ansatz for the N -body Configuration Interaction (FANCI). As demonstrated elsewhere, this formulation includes not only conventional CI and coupled cluster (CC) approaches, but also matrix-product states, tensor network states, and a wide variety of wave functions based on composite bosons and composite fermions, including many flavors of geminals. …”
Section: Introductionmentioning
confidence: 99%
“…3 For weakly correlated systems where a single-reference (SR) wave function provides a good starting point, CC yields remarkably accurate results even with only single and double excitations (CCSD). Improved by approximate inclusion of triple excitations (such as CCSD[T], 4 CCSD(T) 5 or iCCSDn 6 ), this method can give results with chemical accuracy (∼1 kcal mol −1 error), motivating efforts toward numerical realization for systems of impressive size. 7,8 Deficiencies of the single determinantal reference may induce a breakdown of SR-based CC when when applied to strongly correlated systems (e.g., molecules with dissociating covalent bonds).…”
Section: Introductionmentioning
confidence: 99%